Crohn's disease-associated AIEC inhibiting intestinal epithelial cell-derived exosomal let-7b expression regulates macrophage polarization to exacerbate intestinal fibrosis. (31st December 2023) - Xu, Yihan; Qian, Wenwei; Huang, Liangyu; Wen, Weiwei; Li, Yi; Guo, Feilong; Zhu, Zhenxing; Li, Zhun; Gong, Jianfeng; Yu, Zeqian; Zhou, Yan; Lu, Nan; et al.
ABSTRACT: The interaction between adherent-invasive Escherichia coli (AIEC) and intestinal macrophages is implicated in the pathogenesis of Crohn's disease (CD). However, its role in intestinal fibrogenesis and the underlying molecular mechanisms are poorly understood. In addition, miRNAs such as let-7b may participate in AIEC-macrophage interactions. In this study, we identified that the colonization of AIEC in the ileum was associated with enhanced intestinal fibrosis and reduced let-7b expression by enrolling a prospective cohort of CD patients undergoing ileocolectomy. Besides, AIEC-infected IL-10 −/− mice presented more severe intestinal fibrosis and could be improved by exogenous let-7b. Mechanistically, intestinal macrophages were found to be the main target of let-7b. Transferring let-7b-overexpressing macrophages to AIEC-infected IL-10 −/− mice significantly alleviated intestinal fibrosis. In vitro, AIEC suppressed exosomal let-7b derived from intestinal epithelial cells (IECs), instead of the direct inhibition of let-7b in macrophages, to promote macrophages to a fibrotic phenotype. Finally, TGFβR1 was identified as one target of let-7b that regulates macrophage polarization. Overall, the results of our work indicate that AIEC is associated with enhanced intestinal fibrosis in CD. AIEC could inhibit exosomal let-7b from IECs to promote intestinal macrophages to a fibrotic phenotype and then contributed to fibrogenesis. Thus, anti-AIEC or let-7b therapy may serve as novel therapeutic approaches to ameliorate intestinal fibrosis. Plain Language Summary: What is the context? Adherent-invasive Escherichia coli (AIEC) plays an important role in the pathogenesis of Crohn's disease (CD) and has a strong association with intestinal fibrosis in animal models. However, how these bacteria contribute to intestinal fibrosis in CD patients is still unclear. The plasticity of macrophages is crucial in immune tolerance and tissue repair in the gastrointestinal tract, and the abnormal interaction between macrophages and gut bacteria triggers the fibrogenesis in the intestine. The association between the miRNA let-7b and fibrosis process has been widely reported in many tissues, except the intestine. What is new? AIEC colonization in the terminal ileum is associated with severe intestinal fibrosis in CD patients and the let-7b plays an anti-fibrotic role in intestinal fibrosis. Intestinal macrophages are the key modulator of AIEC-induced fibrosis and can be promoted to an antifibrotic phenotype through let-7b-targeted TGFβR1 inhibition. AIEC suppresses intestinal epithelial cell-derived exosomal let-7b to promote intestinal macrophages to a fibrotic phenotype, rather than a direct effect on macrophage regulation. What is the impact? Anti-AIEC and let-7b therapy may serve as potential therapeutic strategies to reduce intestinal fibrosis in CD in the future.